2017
DOI: 10.1111/dom.12893
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of metformin in gestational diabetes mellitus

Abstract: Metformin use during pregnancy is controversial and there is disparity in the acceptance of metformin treatment in women with gestational diabetes mellitus (GDM) in Australia. Despite short term maternal and neonatal safety measures, the placental transfer of metformin during GDM treatment and the absence of long-term safety data in offspring has regulators and prescribers cautious about its use. To determine the current role in GDM management, this literature review describes the physiological changes that oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 76 publications
(130 reference statements)
1
33
0
4
Order By: Relevance
“…Similar concentrations of metformin in the umbilical artery and umbilical vein suggest negligible metformin metabolism by the fetus (244). Several meta-analyses that studied the teratogenic effect of metformin on embryonic development found that this drug carries no increased risk for congenital malformations(245, 246) and is currently classified as category B in the United States and as category C in Australia (247, 248). Similarly, no excess of fetal or neonatal complications could be demonstrated when the administration of metformin was compared to glyburide and insulin(249).…”
Section: Safety Of Metformin During Pregnancymentioning
confidence: 99%
“…Similar concentrations of metformin in the umbilical artery and umbilical vein suggest negligible metformin metabolism by the fetus (244). Several meta-analyses that studied the teratogenic effect of metformin on embryonic development found that this drug carries no increased risk for congenital malformations(245, 246) and is currently classified as category B in the United States and as category C in Australia (247, 248). Similarly, no excess of fetal or neonatal complications could be demonstrated when the administration of metformin was compared to glyburide and insulin(249).…”
Section: Safety Of Metformin During Pregnancymentioning
confidence: 99%
“…(2017), принимая во внима-ние краткосрочные данные о материнской и неонаталь-ной безопасности, отмечают, что плацентарный перенос метформина и отсутствие долгосрочных результатов по безопасности у потомства обосновывают осторож-ность в использовании препарата при беременности [73]. Авторы соглашаются с благоприятным балансом дока-зательств, подтверждающих преимущества безопасно-сти использования метформина для матери и ребенка при ГСД.…”
Section: сахарный диабет Diabetes Mellitusunclassified
“…Risiken sind weder für die Mütter noch für die ungebore-nen Kinder bekannt. Zahlreiche Länder weltweit setzen bereits Metformin anstelle von Insulin zur medikamentösen Therapie des GDM ein [14].…”
Section: Stoffwechselkontrolle Im Art-zyklusunclassified